Prospective Comparative Quality Control Study of a Novel Gravity-Driven Hollow-Fiber Whole Blood Separation System for the Production of Canine Blood Products - Lehmann, Hendrik; Hindricks, Esther; Hassdenteufel, Esther Maria; Moritz, Andreas; Bauer, Natali (Frontiers in Veterinary Science, 2019)
The aim of this prospective study was to compare quality of blood products produced either by a novel gravity-driven hollow-fiber separation system (HF) or by centrifugation (C). Whole blood was obtained from thirty-one healthy non-greyhound canine blood donors and separated into fresh frozen plasma and packed red blood cells using either HF or C in a university teaching hospital. Red blood cell (RBC) count, albumin and fibrinogen concentration, prothrombin time (PT), activated partial thromboplastin time (aPTT) and coagulation factor activity (FV, FVIII), von Willebrand Factor (vWF), and antithrombin activity were assessed. Plasma obtained with the HF showed a significantly higher median PT (9.4 vs 7.9 sec, P<0.0001) and aPTT (14.9 vs 13.1 sec, P=0.006) than plasma prepared with C. Lower albumin (21.7 vs 23.5 g/l, P=0.0018) and fibrinogen (1.0 vs 1.5 g/l, P<0.0001) concentrations and activities of FV (105 vs 114 %, P=0.0007) and antithrombin (104 vs 117 %, P=0.0006) were seen in blood products obtained with the HF. In contrast, vWF was not affected by the method of plasma separation. Compared to HF, RBC count as well as hematocrit were significantly higher (8.0 vs 8.9 1012/l, P=0.0218; 0.57 vs 0.62 l/l, P=0.0012) when blood products were prepared with C. In conclusion, higher quality of blood products especially regarding coagulation parameters and RBCs was achieved by using C compared to HF. Despite the statistical significances, however, the clinical relevance has to be further elucidated. Nevertheless, HF provides an alternative to produce blood products if a centrifuge is not available.